MODELLING OF A LOW PHASE NOISE RING OSCILLATOR USING SILICON GERMANIUM HETEROJUNCTION BIPOLAR TRANSISTORS - Sinha, Saurabh (University of Pretoria, 2016)
Dissertation (MEng)--University of Pretoria, 2016.